Phenolics content and antioxidant properties of Strobilanthes crispus as affected by different extraction solvents - Haida, Zainol; Nakasha, Jaafar Juju; Hakiman, Mansor (Farm to Fork Foundation, 2020)
Strobilanthes crispus or locally known as Pecah Kaca among Malaysian is a medicinal plant that belongs to the family Acanthaceae. S. crispus is an ethnomedicinal plant with high antioxidant content and is indicated in the treatment of diabetes, cancer, and hypertension. This study was conducted to study the phenolics content and antioxidant properties of S. crispus leaf as affected by different concentrations of extraction solvents. In this study, water and various concentrations (25, 50, 75 and 100%) of methanol and acetone in water were used as extraction solvent of S. crispus dried leaves. The antioxidant properties of S. crispus were measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) (free radical scavenging activity and ferric reducing antioxidant power (FRAP) assays. The highest polyphenols and phenolic acids content were recorded in 50% acetone extract with 10.80 and 33.86 mg GAE/g DW, respectively. Meanwhile, the highest total flavonoids content (4.98 mg QE/g DW) was obtained in 100% acetone extract. In the antioxidant analysis, the highest DPPH free radical scavenging activity was exhibited from 75% acetone extract with 24.88 mg TE/g DW and the highest FRAP value was obtained from 25% acetone extract with 47.21 mg TE/g DW. In conclusion, acetone was found to be the most suitable extraction solvent for phenolics content and antioxidant properties of S. crispus leaf in this study.